Modification and validation of the Birmingham Vasculitis Activity Score (version 3). Issue 12 (3rd December 2008) - Mukhtyar, C; Lee, R; Brown, D; Carruthers, D; Dasgupta, B; Dubey, S; Flossmann, O; Hall, C; Hollywood, J; Jayne, D; Jones, R; Lanyon, P; et al.
Abstract : Background: Comprehensive multisystem clinical assessment using the Birmingham Vasculitis Activity score (BVAS) is widely used in therapeutic studies of systemic vasculitis. Extensive use suggested a need to revise the instrument. The previous version of BVAS has been revised, according to usage and reviewed by an expert committee. Objective: To modify and validate version 3 of the BVAS in patients with systemic vasculitis. Methods: The new version of BVAS was tested in a prospective cross-sectional study of patients with vasculitis. Results: The number of items was reduced from 66 to 56. The subscores for new/worse disease and persistent disease were unified. In 313 patients with systemic vasculitis, BVAS(v.3) correlated with treatment decision (Spearman's r s  = 0.66, 95% CI 0.59 to 0.72), BVAS1 of version 2 ( r s  = 0.94, 95% CI 0.92 to 0.96), BVAS2 of version 2 in patients with persistent disease ( r s  = 0.60, 95% CI 0.21 to 0.83), C-reactive protein levels ( r s  = 0.43, 95% CI 0.31 to 0.54), physician's global assessment ( r s  = 0.91, 95% CI 0.89 to 0.93) and vasculitis activity index ( r s  = 0.88, 95% CI 0.86 to 0.91). The intraclass correlation coefficients for reproducibility and repeatability were 0.96 (95% CI 0.95 to 0.97) and 0.96 (95% CI 0.92 to 0.97), respectively. In 39 patients assessed at diagnosis and again at 3 months, the BVAS(v.3) fell by 17 (95% CI 15 to 19) units (p<0.001, paired t test). Conclusion: BVAS(v.3) demonstrates convergence with BVAS(v.2), treatment decision, physician global assessment of disease activity, vasculitis activity index and C-reactive protein. It is repeatable, reproducible and sensitive to change. The new version of BVAS is validated for assessment of systemic vasculitis.